Direct Bonding Mechanism of ALD-Al2O3 Thin Films. (25th March 2015) - Beche, E.; Fournel, F.; Larrey, V.; Rieutord, F.; Morales, C.; Charvet, A.-M; Madeira, F.; Audoit, G.; Fabbri, J.-M.
Abstract : Direct bonding mechanism of amorphous ALD alumina has been investigated from room temperature up to 1200°C. By considering the evolution with temperature of free alumina surfaces and bonded configuration we highlight strong interaction between oxidant species and defect generation through interfacial oxidation. In the first case, the combination of internal stress and adhesion loss by dry O2 oxidation results in blister formations, whereas in the case of bonding structures, wet oxidation with H2 production at Silicon-Alumina interfaces explains void formation. Based on these established mechanisms we provide insights on alumina layer integration within a large temperature range.